Rasagalor Coffee Education Tourist Attraction Design based on Halal Tourism in Mekarmanik Village, Bandung Regency - Burhanudin, Hani; Weishaguna, Weishaguna; Saraswati, Saraswati; Asyiawati, Yulia; Ahmad Barwanto, Lutfhi; Arianto Widagdo, Rama; Pratama, Aldy; Rifky Ferbiyandani, Mochamad; Nurhasanah, Halimah; Defannya Serdani, Sherly (KnE Social Sciences, 2023)
The halal tourism concept is a contemporary tourism development concept that is currently implemented around the world. Halal tourism does not only relate to producing halal products, but also every other aspect of Islamic beliefs, including developing domains that support Islamic activities. This article aims to explore designs for tourist attractions based on the halal tourism concept. The research will take place in Mekarmanik Village, Cimenyan District, Bandung Regency. The location experiences three major issues, which are farmers’ mindset who prefers selling straight to wholesalers for low prices compared to further processing products for higher prices; forest land and coffee vegetation utilization for educational objects; and integration of potential colonial sites to increase local community livelihood. Therefore, the design will aim to include means that could help increase the local community’s knowledge through site planning and 3D designs of a product processing room, product marketing storefront, coffee forest educational hiking trail, and dan colonial coffee garden educational room. Required data will be gathered from literature studies, field observations, and focus group discussions (FGDs). Afterward, collected data will be analyzed using design elements needs analysis and functional relations analysis. Later, design results may bring solutions that would be able to increase local farmers’ and community livelihoods. Keywords: halal tourism, mekarmanik, design, educational area, rasagalor coffee